Functional Genomics of PCOS. Issue 9 (September 2015) - McAllister, Jan M.; Legro, Richard S.; Modi, Bhavi P.; Strauss, Jerome F.
<x xml:space="preserve">Abstract</x> ABSTRACT Polycystic ovary syndrome (PCOS) is a common disorder affecting 5% to 7% of women of reproductive age worldwide. The syndrome is characterized by increased ovarian androgen biosynthesis, anovulation, and infertility. Its etiology is poorly understood. Hyperandrogenemia (hyperandrogenism) is a hallmark of the disorder and has been included as an essential element in all "consensus" diagnosis schemes. There is strong evidence for a genetic component in PCOS from familial clustering and twin studies. Genome-wide association studies (GWASs) in Han Chinese women identified several PCOS candidate loci in or near the genes encoding receptors for LHCGR, FSHR, DENND1A, INSR, ZNF217, YAP1, RAB5B, THADA, and C9orf3. The association of several of these loci with PCOS was confirmed in studies conducted in European populations; these loci include FSHR, LHCGR, and DENND1A, as well as RAB5B and THADA. However, there is no convincing evidence at present that the variants identified in these genes are functionally significant and contribute to the PCOS phenotype. This review examined the functional roles of strong candidate PCOS loci identified in the GWASs and subsequently replicated in other populations, with primary focus on FHSR, LHCGR, INSR, and DENND1A. Previous studies have shown that ovarian theca cells are the primary source of high levels of androgens in women with PCOS and that a variant of DENND1A, called DENND1A.V2, may play a major role in PCOS. This variant of DENND1A is a new diagnostic and therapeutic target for PCOS. Forced overexpression of DENND1A.V2 in cultured theca cells from women without PCOS increases androgen production converting them to a PCOS phenotype, whereas blocking V2 expression in PCOS theca cells markedly reduces androgen secretion. The authors propose that these GWAS candidate genes comprise a hierarchical signaling network by which DENND1A, LHCGR, INSR, RAB5B, adapter proteins, and their associated downstream signaling cascades converge to regulate theca cell expression and androgen biosynthesis. These findings may lead to new diagnostic and therapeutic approaches for women with PCOS. DENND1A.V2 is present in the urine, and its increased urinary excretion could be a diagnostic biomarker for PCOS. Having such a molecular marker may identify a population of young girls who develop the disorder at adrenarche or pubarche and allow earlier intervention. Future studies should investigate the possibility that DENND1A.V2 is a biomarker for PCOS and examine its role in predicting response to common treatments for women with PCOS.